Exploring the Influence of School Climate on Teaching and Learning of Agriculture at Senior Secondary Schools in Eswatini - Alfred Tsikati; Dumisa Dlamini (E-Journal of Humanities, Arts and Social Sciences)
School climate is the quality and character of school life reflected in its norms, goals, values, interpersonal relationships, teaching and learning practices and organizational structures. No study has been conducted to assess the school climate that exists in Eswatini schools. Thus, this study sought to assess the school climate that exists in senior secondary schools influencing the teaching and learning of agriculture in Eswatini. The study utilized a qualitative research approach employing a phenomenological research design. Purposive sampling was used to sample 25 agriculture teachers in Eswatini. An interview guide was used to collect data in February 2024. Trustworthiness was ensured by addressing issues related to credibility, transferability, dependability and confirmability. Thematic analysis was used to analyse the qualitative data. The study concluded that the climate in Eswatini schools does not fully support the teaching and learning of agriculture. The study therefore, recommended a review of the school policies set by the Ministry of Education and Training; in order to create a conducive school climate that supports the teaching and learning of agriculture in senior secondary schools in Eswatini. The study revealed strategies that can be used to improve the school climate in senior secondary schools needed for the teaching and learning of agriculture in Eswatini.